Association of various socio demographic factors with knowledge and practice regarding menstrual hygiene among school going adolescent girls of Jaipur city - Sharma, Nikita; Shekhawat, Rekha (International Journal Of Community Medicine And Public Health, 2019)
Background: There is lack of information on the process of menstruation, the physical and psychological changes associated with puberty and proper requirements for managing menstruation. Hence this community based study was carried out with the objective to assess the level of knowledge and practice regarding menstrual hygiene and their association with sociodemographic factors among school going adolescent girls. Methods: A descriptive, cross sectional study was conducted among 996 adolescent girls of senior secondary schools of Jaipur city. Results: It was evident that 80.72% participants were aware about menstruation before their menarche. Majority (68.07%) used sanitary pad as absorbent material. 34.53% changed the pad at least 3 times or more in a day. 29.21% cleaned the genitalia twice or more than 2 times a day. 86.14% participants were restricted to do religious activities. Significant association was found between type of absorbent used socio economic status, mother’s education. Conclusions: There is strong need to improvise and promote good menstrual hygiene knowledge and practices among adolescent girls. Improving mother’s knowledge on menstrual hygiene management can go a long way in improving menstrual hygiene practice.